Branding dalam Dunia Public Relations - Laili, Siti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims for researchers who want to know in depth about Le Minerale's branding strategy in developing bottled drinking water products. using observation and interview data collection techniques. Observations were made by researchers by observing Le Minerale's Public Relations activities in developing bottled drinking water products. The results of this research conclude that branding public relations for Le Minerale products uses branding public relations strategies in developing Le Minerale products, namely the Hardball Manifesto Strategy, Sensory Marketing.